Social Estates, Occupation, and HISCO: A New Study of Odesa in 1897 - Brik, Tymofii (East/West, 2022)
Odesa was one of the largest and most important cities in the Russian Empire. Numerous studies have addressed the economic development and social structure of Odesa, but there are some gaps in the knowledge of the social stratification during the nineteenth century. Although most studies of the social and economic histories of Ukraine provide qualitative or highly aggregated quantitative data, micro-data at the level of individuals and households in Ukraine are rare. This paper provides new micro-data from the 1897 census in Odesa. It is the first attempt to code occupations of Odesa workers according to the Historical International Standard Classification of Occupations (HISCO). Of the 2,435 individuals in the 457 sampled households analyzed, 1,443 individuals demonstrate 86 of the unique occupations coded with the international HISCO scheme. The analysis compares these HISCO occupations by the social estates, the gender, and the language of the surveyed individuals. The study confirms several old hypotheses but also unearths new findings regarding the number of urban females involved in service and sales occupations.